Conceptual design report of the MPD Cosmic Ray Detector (MCORD). (25th November 2021) - Bielewicz, M.; Bancer, A.; Barabanov, M.; Chlopik, A.; Czarnynoga, M.; Dabrowski, D.; Dudzinski, A.; Dziedzic, A.; Grodzicka-Kobylka, M.; Grzyb, J.; Grodzicki, K.; Jaworska, E.; et al.
Abstract: This report presents a concept of constructing a detector dedicated for detection of muons observed during measurements carried out at the MPD (Multi-Purpose Detector) detector that is currently under construction at the NICA facility, Russia, Dubna. It has been proposed to design and build an additional detector that will complement the current MPD set and increase its measurement capabilities. The main goal of this project is to provide information from cosmic muons that pass the MPD detector in both in-beam and off-beam experiments. Hence, the detector is called the MPD COsmic Ray Detector (MCORD).The conceptual design of MCORD is proposed by a Polish consortium NICA-PL comprising several Polish scientific institutions. The data from cosmic ray muons could be used as a trigger for calibration of other detection systems comprising the MPD detector. Large surface covered by the MCORD offers also possibility for efficient registration of muons generated in expanding atmospheric showers induced by distant sources. Moreover, beyond some energy threshold, observation of muons originating from decays of collision products will also be possible. In this report examples of the MCORD functionality as a part of the MPD detector are presented. The MCORD is designed as a universal, fast triggering system built as a modular reconfigurable construction. The detection system will be based on plastic scintillators equipped with wavelength shifting fibers, and silicon photomultipliers (SiPM) will be used for scintillation readout. The online analysis of received signals will be performed using digital FPGA modules. Due to the modular design, the same system (its small part) can be used for both laboratory testing of other MPD sub-detectors, and the calibration of these detectors after placing them inside the MPD in off-beam mode. The full detector will support these systems as an additional trigger, calibrator, and muon identifier during the normal operation of the MPD detector with the beam. Thanks to its unique construction, it will expand the possibilities of collecting scientific data of the MPD detector with astrophysical observations. The publication will show the assumptions of the mechanical structure and electronic systems of the planned detector. The installation site of the detector as part of the MPD detector will be described in detail. In the following, the results of simulations made in preparation for this project will be presented. In particular, simulations with the CORSIKA code present angular distributions of particles in cosmic showers in the Dubna city region. Since muons dominate the cosmic ray showers, the MPD detector response to expected cosmic muon flux was also simulated. The results provide information about the muon cut-off thresholds depending on the MPD detector composition during the installation campaign. Simulations of muon events that could be used for MPD subsystems calibration were also performed. The results shown for various configuration of MCORD detector modules will enable the estimation of the time necessary to perform such tests in the future. Simulations with UrQMD model shows the muon abundances due to beam-beam collisions. Approximately 90% of muons are created from pions, whereas the number of muons that reach the MCORD detector is 10 times greater than the number of pions. The MPD detector response was also simulated under the influence of a stream of various particles, especially muons. It shows energy dependence of muon transmission coefficient for MPD with and without ECal assembled. Assuming requirement for muon transmission above 95%, the muon cut-off thresholds are 1.6 GeV and 2.0 GeV, respectively. MCORD detector performance evaluation is also reported. In the case when we used scintillators with one fiber with a diameter of 1 mm, the time resolution of about 1.0 ns was recorded, which corresponds to the positional accuracy (σx ) of 7.1 cm. The results of laboratory tests show that application of a 2 mm diameter WLS fiber instead of the previously used 1 mm diameter fiber improves the time resolution to 0.80 ns.